Suksesi Kepemimpinan Arab Pra-Islam dan Periode al-KhulafÃ¢â al-Râshidûn - Biyanto, Biyanto (ISLAMICA: Jurnal Studi Keislaman, 2006)
This article analyses the character and nature of succession in the Pre-IslamicArabic society and in the period of al-KhulafÃ¢â al-Rashidûn. It assumes that both periodsshare a lot in common in terms of conditions of leadership, which include seniority,bravery, generosity, good and noble family background, and the ability to safeguard thetribe. The principle of consultation (mushâwarah), which Islam talks about on manyoccasions, is also present in the two periods. This is despite the fact that during theperiod of al-KhulafÃ¢â al-Râshidûn there were such practices as direct election âin the caseof Abû Bakr and âAlÃ® b. Abî Tâlib-, appointment by the former caliph âin the case ofâUmar b. Khattâb- and election by a committee appointed by the caliph in the case ofâUthmÃ¢n b. âAffÃ¢n.